2017
DOI: 10.1177/0731684417725584
|View full text |Cite
|
Sign up to set email alerts
|

Sisal (Agave sisalana) fibre and its polymer-based composites: A review on current developments

Abstract: Nowadays, it has been global demand to overcome the abundant use of synthetic fibres with respect to save the environment. Sisal fibre is one of the widely used natural fibre and being used as reinforcement for polymer-based composites on account of its excellent properties. This review article deals a brief description of sisal fibre along with its recent applications and characterization of its polymer-based composites in terms of mechanical properties, thermal properties and tribological and water absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 121 publications
(146 reference statements)
1
45
0
2
Order By: Relevance
“…Extraction assays have led to the obtaining of a 5.9 ± 1.4% of fibre (on the basis of dry leaves). Other authors have found a fibre content around 4% for sisal leaves [32,33].…”
Section: Plant Characterizationmentioning
confidence: 86%
See 1 more Smart Citation
“…Extraction assays have led to the obtaining of a 5.9 ± 1.4% of fibre (on the basis of dry leaves). Other authors have found a fibre content around 4% for sisal leaves [32,33].…”
Section: Plant Characterizationmentioning
confidence: 86%
“…Singha and collaborators [37] found an increase in mechanical properties, mainly in impact behaviour, for composites up to 30% of agave fibres, also using polystyrene as matrix; they have also demonstrated that the size of the is an important factor to take into account. Other authors, working with Agave tequilana fibres [33], also found that, for compression moulding and PP composites, 30% of fibre provides the best mechanical results. Cisneros-López and collaborators [41] found that rotationally moulded PLA composites with 10% of agave fibres (agave tequilana) does not change elastic modulus, while higher fibre ratios lead to the reduction of this property; on the other hand, compression moulded PLA allowed increasing the elastic modulus of net PLA by a 14% for 30% composites, while 40% fibre composites had an elastic modulus 13% lower.…”
Section: Composites Characterizationmentioning
confidence: 90%
“…The S+R and S+C composites presented a slightly lower endothermic peak value compared to non-hybrid S composites (approximately 136.5 and 137.8 compared to 140.5 • C). This can be explained by the fact that composites with higher natural fiber content shows a higher water absorption [5]. Furthermore, the exothermic peak found around 365 • C is attributed to the decomposition of cellulose/lignin and the matrix [47][48][49].…”
Section: Dscmentioning
confidence: 99%
“…One method to increase their performance is the hybridization. In this context, natural fiber-reinforced hybrid composites, which contain one or more types of fiber are gaining growing research interest [1][2][3][4][5][6]. Both natural and synthetic fibers can be used to produce hybrid composites [7].…”
Section: Introductionmentioning
confidence: 99%
“…A esterificação por acetilação é uma técnica de substituição química eficaz que diminui a tendência hidrofílica das fibras naturais. (TSERKI V. et al, 2005;SAHU, P.;et al, 2017;SANTOS E. P. Dos. 2017;).…”
Section: Introductionunclassified